Resource intensity of the digital transformation in Germany - Katharina Milde; Mark Meyer; Roman Kirchdorfer; Daniel Haack (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
The project “Digitalisation and natural resources” (DigitalRessourcen) analyzed the resource intensity of digitalization in Germany. Various micro- and macro-level analyses were conducted and areas for shaping sustainable digitalization were identified. At the micro-level, the resource requirements and environmental impacts of digital products and services were calculated on the basis of case studies using life cycle assessment principles. At the macro-level, input-output models were applied to determine the need for raw materials and the CO2 emissions of the digitalization in Germany for the national economy. The micro-level analyses confirmed the expected correlation between raw material use, energy use, and global warming potential. The main causes here were identified in the manufacturing and use phases. Macro-level analyses revealed that, besides domestic demand dependencies, the close links between the German economy and international trade could be an obstacle to reducing the raw material and CO2 intensity of digitalization.